Analisis dan Perancangan Aplikasi Sistem Informasi Akuntansi Penggajian Karyawan Menggunakan Microsoft Access 2016 (Studi Kasus pada Toserba Fajar Luragung - Kuningan) - Amaldia Sonnya Budiarto; Darya Setia Nugraha; Sudjana; Arif Afriady; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Toserba Fajar is a supermarket that sells various household needs as well as women's and men's fashion products. The employee payroll system implemented by Fajar Department Store is done manually and has not been integrated. Beside that, Fajar Department Store does not yet have an employee database, so there are several problems such as complaints from employees demanding salary increases, payroll transactions that take a long time, and there are no experts who capable in the field of IT, and there is no payroll report so that the central manager cannot supervise the payroll activities carried out. This research is a research conducted using the SDLC (Software Development Life Cycle) method as a grand theory in analyzing system design. By designing this application, the authors hope that the Fajar Department Store company can more easily carry out employee payroll transactions.